2008
DOI: 10.1111/j.1475-5661.2008.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Language use on the move: sites of encounter, identities and belonging

Abstract: The role of language in relation to identity formation has received relatively little attention from geographers. Here, drawing on empirical research with Somali young people (aged 11–18) now living in the UK, we explore the role that choice and use of language play in how young people make sense of their identities and affiliations within the specific situated context of everyday encounters at home, and school. In doing so, we explore the role of language as a situated practice in (re)making identities in loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 24 publications
0
46
0
3
Order By: Relevance
“…to everyday life encounters (Amin 2005, 9). Similarly, by focusing on immigrants and their children, a few scholars have investigated forms of belonging that no longer identify purely with territory, but, for instance, with linguistic commonality (Valentine et al. 2008) or with transnational networks, images, and memories (Bromley 2000; Colombo et al.…”
Section: Rethinking Belonging Beyond Exclusionmentioning
confidence: 99%
“…to everyday life encounters (Amin 2005, 9). Similarly, by focusing on immigrants and their children, a few scholars have investigated forms of belonging that no longer identify purely with territory, but, for instance, with linguistic commonality (Valentine et al. 2008) or with transnational networks, images, and memories (Bromley 2000; Colombo et al.…”
Section: Rethinking Belonging Beyond Exclusionmentioning
confidence: 99%
“…English is acquired most successfully when a child's first language has been allowed to develop alongside it (Baker 2000, Cummins 2000, Skutnabb-Kangas 2000. Valentine et al (2008) suggested that this might include the provision of more opportunities and incentives for schools to broaden the curriculum to incorporate more modern languages teaching -recognizing the increasingly diverse range of linguistic needs and competencies of their pupils and parents/families thereby promoting multilingualism. The issues of language, identity and social change in Scotland should be discussed in schools.…”
Section: Resultsmentioning
confidence: 99%
“…Further, they show that the Polish language school creates a space 'where cultural differences are being articulated' and are in process (Valentine et al 2008: 376). The spaces created by this form of tourism enable (re)articulations of cultural identities in place, rather than focusing on where these identities were originally formed (Valentine et al 2008). Citing Wenger (1998: 215), Valentine et al (2008: 377) argue that language learning 'transforms who we are .…”
Section: The Effect Of Polish Heritagementioning
confidence: 97%